Chronic E-Cigarette Use Impairs Endothelial Function on the Physiological and Cellular Levels. Issue 11 (27th October 2022) - Mohammadi, Leila; Han, Daniel D.; Xu, Fengyun; Huang, Abel; Derakhshandeh, Ronak; Rao, Poonam; Whitlatch, Adam; Cheng, Jing; Keith, Rachel J.; Hamburg, Naomi M.; Ganz, Peter; Hellman, Judith; et al.
Abstract : Background: The harmful vascular effects of smoking are well established, but the effects of chronic use of electronic cigarettes (e-cigarettes) on endothelial function are less understood. We hypothesized that e-cigarette use causes changes in blood milieu that impair endothelial function. Methods: Endothelial function was measured in chronic e-cigarette users, chronic cigarette smokers, and nonusers. We measured effects of participants' sera, or e-cigarette aerosol condensate, on NO and H2 O2 release and cell permeability in cultured endothelial cells (ECs). Results: E-cigarette users and smokers had lower flow-mediated dilation (FMD) than nonusers. Sera from e-cigarette users and smokers reduced VEGF (vascular endothelial growth factor)-induced NO secretion by ECs relative to nonuser sera, without significant reduction in endothelial NO synthase mRNA or protein levels. E-cigarette user sera caused increased endothelial release of H2 O2, and more permeability than nonuser sera. E-cigarette users and smokers exhibited changes in circulating biomarkers of inflammation, thrombosis, and cell adhesion relative to nonusers, but with distinct profiles. E-cigarette user sera had higher concentrations of the receptor for advanced glycation end products (RAGE) ligands S100A8 and HMGB1 (high mobility group box 1) than smoker and nonuser sera, and receptor for advanced glycation end product inhibition reduced permeability induced by e-cigarette user sera but did not affect NO production. Conclusions: Chronic vaping and smoking both impair FMD and cause changes in the blood that inhibit endothelial NO release. Vaping, but not smoking, causes changes in the blood that increase microvascular endothelial permeability and may have a vaping-specific effect on intracellular oxidative state. Our results suggest a role for RAGE in e-cigarette-induced changes in endothelial function.